Complex interactions among MHC haplotypes in multiple sclerosis: susceptibility and resistance. - Dyment, D; Herrera, B; Cader, M; Willer, C; Lincoln, MR; Sadovnick, A; Risch, N; Ebers, G (2005)
Mechanisms for observed associations within the major histocompatibility complex (MHC) and autoimmune diseases including multiple sclerosis (MS) remain uncertain. Genotyping of the HLA Class II DRB1 locus in 4347 individuals from 873 multiplex families with MS highlights the genetic complexity of this locus. Excess allele sharing in sibling pair families lacking DRB1*15 and DRB1*17 (58.5% sharing; P=0.012) was comparable to that seen where parents were DRB1*15 positive (62%, P=0.0006). DRB1*17 (P=0.00027) was clearly established as an MS susceptibility allele in addition to DRB1*15 (P<10(-14)). DRB1*14 showed striking under-transmission (P=0.000032) to affected offspring newly establishing this allele as a broadly acting resistance factor. Trans interactions were seen in both DRB1*15 and non-DRB1*15 bearing genotype combinations. DRB1*08 was transmitted preferentially with DRB1*15 (P=0.0114) and, in the presence of DRB1*08, the transmission of DRB1*15 was almost invariable (37 transmissions to one non-transmission). DRB1*01 was under-transmitted to offspring in the presence of DRB1*15 (P=0.019). Both DRB1*01 and DRB1*14 haplotypes carry DQA1*01-DQB1*05 alleles, suggesting a common DQ-related mechanism for the protection mediated by these haplotypes. These studies demonstrate that it is the Class II genotype that determines susceptibility and resistance to MS. By analogy with celiac disease and type I diabetes, the pattern of susceptibility strongly supports an autoimmune aetiology.